Continental philosophy a very short introduction - Critchley, Simon 1960- (Very short introductions, 2001)
Critchley discusses the ideas and approaches of philosophers such as Kant, Hegel, Nietzsche, and Husserl, and introduces key concepts such as existentialism, nihilism, and phenomenology by explaining their place in the continental tradition